Pengaruh Carbon Emission Disclosure Terhadap Nilai Perusahaan Dengan Kinerja Lingkungan Sebagai Variabel Pemoderasi - Sheila Ayu Rahmanita (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2020)
This study aims to empirically know the influence of Carbon Emission Disclosure (CED) on firm value with environmental performance as a moderating variable. This research uses a quantitative approach by using secondary data. The sample was selected purposive sampling with a population of non-financial companies listed in Indonesia Stock Exchange from 2016-2018. The hypothesis was tested using SPSS 21 program with Moderated Regression Analysis(MRA) technique. The results of the research showed that CED and environmental performance were significantly positive effect on firm value. So it can be concluded that CED and PROPER can be used as a corporate signal to increase firm value. In addition, environmental performance can moderate the relationship between CED and firm value with pure moderator type.